Emperor worship and Roman religion - Gradel, Ittai (Oxford classical monographs., 2002)
"This book presents the first study of emperor worship among the Romans themselves, both in Rome and in its heartland Italy. It argues that emperor worship was indeed perfectly in keeping with Roman religious tradition, which has been generally misunderstood by a posterity imbued in radically different notions of the relationship between man and the divine."--Jacket.